Local history between fact and fabrication: the history of Ningbo during the Tang Dynasty - Hirzel, Thomas (Taylor and Francis, 2020)
Ningbo in the southeastern Chinese province of Zhejiang emerged as a city during the Tang dynasty (618–907), and was known at that time as Mingzhou. On the question where the administrative, political and economic center of the Ningbo region was located between 738 and 821 the various source materials either remain silent or tell very different stories. In this study I re-visit and discuss the three main theories using textual analysis combined with archaeological evidence. On the basis of textual and recent archaeological evidence this study argues that today’s location of Ningbo at Sanjiangkou was the political, economic and cultural center of Eastern Zhejiang over 400 years earlier than previously thought. This clearly demonstrates the geographical and economic importance of the location at Sanjiangkou and the political stability of the region from the end of the Eastern Jin dynasty (317–420).